Trading Volume and Belief Revisions That Differ among Individual Analysts - Barron, Orie E. (The Accounting Review, 1995)
[This study examines the association between trading volume and belief revisions. Most trading volume theories suggest that investors' differential belief revisions cause trading volume. A belief revision is differential if it changes the position of an individual's expectation relative to the distribution of expectations held by others. Thus, I use the correlation between the relative positions of individual analysts' current and prior forecasts of earnings to measure differential belief revisions. In a multiple regression analysis, this correlation measure explains trading volume beyond that explained by prior dispersion in forecasts, which is consistent with Karpoff's (1986) prediction that trading is caused by both differential prior beliefs and differential belief revisions.]